Assessing Africa-Wide Pangolin Exploitation by Scaling Local Data - Ingram, D.J.; Coad, L.M.; Abernethy, K.A.; Maisels, F.; Stokes, E.J.; Bobo, K.S.; Breuer, T.; Gandiwa, Edson; Ghiurghi, A.; Greengrass, E.; Holmern, T.; Kamgaing, T.O.W.; et al. (Wiley, 2018)
Overexploitation is one of the main pressures driving wildlife closer to extinction, yet broad‐scale data to evaluate species’ declines are limited. Using African pangolins (Family: Pholidota) as a case study, we demonstrate that collating local‐scale data can provide crucial information on regional trends in exploitation of threatened species to inform conservation actions and policy. We estimate that 0.4‐2.7 million pangolins are hunted annually in Central African forests. The number of pangolins hunted has increased by ∼150% and the proportion of pangolins of all vertebrates hunted increased from 0.04% to 1.83% over the past four decades. However, there were no trends in pangolins observed at markets, suggesting use of alternative supply chains. The price of giant (Smutsia gigantea) and arboreal (Phataginus sp.) pangolins in urban markets has increased 5.8 and 2.3 times respectively, mirroring trends in Asian pangolins. Efforts and resources are needed to increase law enforcement and population monitoring, and investigate linkages between subsistence hunting and illegal wildlife trade.